A dominant-negative SOX18 mutant disrupts multiple regulatory layers essential to transcription factor activity. Issue 19 (27th September 2021) - McCann, Alex J; Lou, Jieqiong; Moustaqil, Mehdi; Graus, Matthew S; Blum, Ailisa; Fontaine, Frank; Liu, Hui; Luu, Winnie; Rudolffi-Soto, Paulina; Koopman, Peter; Sierecki, Emma; Gambin, Yann; et al.
Abstract: Few genetically dominant mutations involved in human disease have been fully explained at the molecular level. In cases where the mutant gene encodes a transcription factor, the dominant-negative mode of action of the mutant protein is particularly poorly understood. Here, we studied the genome-wide mechanism underlying a dominant-negative form of the SOX18 transcription factor (SOX18 RaOp ) responsible for both the classical mouse mutant Ra gged Op ossum and the human genetic disorder Hypotrichosis-lymphedema-telangiectasia-renal defect syndrome. Combining three single-molecule imaging assays in living cells together with genomics and proteomics analysis, we found that SOX18 RaOp disrupts the system through an accumulation of molecular interferences which impair several functional properties of the wild-type SOX18 protein, including its target gene selection process. The dominant-negative effect is further amplified by poisoning the interactome of its wild-type counterpart, which perturbs regulatory nodes such as SOX7 and MEF2C. Our findings explain in unprecedented detail the multi-layered process that underpins the molecular aetiology of dominant-negative transcription factor function.